Trajetórias de vida, estratégias de resistências e protagonismos de professoras quilombolas da Comunidade de Chumbo/Poconé/MT - Pereira, Luciano da Silva (2017)
This study results from an ethnographic investigation made in Nossa Senhora Aparecida do Chumbo Community located in quilombola territory, belonging to Poconé Municipality, in Mato Grosso. It had as objective to know the lives trajectories of quilombolas professors, as well as, to comprehend the resistance processes built by them in front of racial discriminations that experienced during their school and professional route. Methodologically, this investigation is inserted on the qualitative inquiry, using the ethnographic method and oral history according to Denzin and Lincoln (2006), Geertz (2008), and Alberti (2013). For collecting data it was used: the participant observation, semi-structured interviews, field notebook and life history interview. The contributors of the research were five people that teach in the community, two professors that already taught in the locality and three old residents. The theoretical supports were considered, emphasizing: Moura (1988), Freitas (1984), Castilho (2011), Beauvoir (1949), Munanga (2003), Gomes (2013), Hall (2002), and some others. The investigation results show that the negras quilombolas professors had a life trajectory marked by difficulties, however, they did not give up dreaming and they were looking for their professional and personal achievements, creating resistance strategies in front of excluding conditions against them. This research still reveals that, even though, the professors lived racists experiences and speeches such as negra, woman and teacher that devalued them inside and outside school spaces, nonetheless, they chose not to allow themselves to be victimized by those kind of acts, looking through the studies and the teacher profession, respect and deserved personal and professional recognition.